Variation in Institutional Review Board Responses to a Standard Protocol for a Multicenter Clinical Trial - Stair, Thomas O.; Reed, Caitlin R.; Radeos, Michael S.; Koski, Greg; Camargo, Carlos A. (Academic emergency medicine, 2001)
. Multicenter clinical trials require approval by multiple local institutional review boards (IRBs). The Multicenter Airway Research Collaboration mailed a clinical trial protocol to its U.S. investigators and 44 IRBs ultimately reviewed it. Objective: To describe IRB responses to one standard protocol and thereby gain insight into the advantages and disadvantages of local IRB review. Methods: Two surveys were mailed to participants, with telephone follow‐up of nonrespondents. Survey 1 was mailed to 82 investigators across North America. Survey 2 was mailed to investigators from 44 medical centers in 17 U.S. states. Survey 1 asked about each investigator's local IRB (e.g., frequency of meetings, membership), whereas survey 2 asked about IRB queries and concerns related to the submitted clinical trial. Results: Both surveys had 100% response rate. Investigators submitted applications a median of 58 days (interquartile range [IQR], 40‐83) after receipt of the protocol, and IRB approval took an additional 38 days (IQR, 26‐62). Although eight applications were approved with little or no changes, IRBs requested an average of 3.5 changes per site. Changes involved study logistics and supervision for 45%, the research process for 43%, and the consent form for 91%. Despite these numerous requests, all eventually approved the basic protocol, including inclusion criteria, intervention, and data collection. Conclusions: The IRBs showed extreme variability in their initial responses to a standard protocol, but ultimately all gave approval. Almost all IRBs changed the consent form. A national, multicenter IRB process might streamline ethical review and warrants further consideration.